Poor quality vital anti-malarials in Africa - an urgent neglected public health priority. - Newton, P; Green, MD; Mildenhall, D; Plançon, A; Nettey, H; Nyadong, L; Hostetler, D; Swamidoss, I; Harris, G; Powell, K; Timmermans, A; Amin, A; et al. (BioMed Central, 2011)
BACKGROUND: Plasmodium falciparum malaria remains a major public health problem. A vital component of malaria control rests on the availability of good quality artemisinin-derivative based combination therapy (ACT) at the correct dose. However, there are increasing reports of poor quality anti-malarials in Africa. METHODS: Seven collections of artemisinin derivative monotherapies, ACT and halofantrine anti-malarials of suspicious quality were collected in 2002/10 in eleven African countries and in Asia en route to Africa. Packaging, chemical composition (high performance liquid chromatography, direct ionization mass spectrometry, X-ray diffractometry, stable isotope analysis) and botanical investigations were performed. RESULTS: Counterfeit artesunate containing chloroquine, counterfeit dihydroartemisinin (DHA) containing paracetamol (acetaminophen), counterfeit DHA-piperaquine containing sildenafil, counterfeit artemether-lumefantrine containing pyrimethamine, counterfeit halofantrine containing artemisinin, and substandard/counterfeit or degraded artesunate and artesunate+amodiaquine in eight countries are described. Pollen analysis was consistent with manufacture of counterfeits in eastern Asia. These data do not allow estimation of the frequency of poor quality anti-malarials in Africa. CONCLUSIONS: Criminals are producing diverse harmful anti-malarial counterfeits with important public health consequences. The presence of artesunate monotherapy, substandard and/or degraded and counterfeit medicines containing sub-therapeutic amounts of unexpected anti-malarials will engender drug resistance. With the threatening spread of artemisinin resistance to Africa, much greater investment is required to ensure the quality of ACTs and removal of artemisinin monotherapies. The International Health Regulations may need to be invoked to counter these serious public health problems.